Semi-empirical systematics formulas for the (n, p), (n, α), and (n, 2n) reaction cross-sections at 14.5 MeV. (November 2021) - Hingu, Akash; Parashari, Siddharth; Singh, Suraj K.; Soni, Bhargav; Mukherjee, S.
Abstract: New Semi-empirical mass formulas were developed for the (n, p), ( n, α ), and (n, 2n) reaction cross-sections at 14.5 MeV neutron energy by using the literature data available on EXFOR library. The new formulas were derived on the basis of the statistical model considering Q − value dependence. The results obtained from the present exercise were compared with other systematic formulas developed in past years as well as with the experimental literature data reported on EXFOR library. The comparison has been done on the basis of statistical model as well as on the asymmetry parameter dependence. The present work offers an alternative to reproduce nuclear data at 14.5 MeV incident neutron energies. Highlights: New Semi empirical formulas have been developed using semi empirical approach. Statistical model and asymmetry dependence were taking into account. New formulas successfully reproduce (n, p), (n, a), and (n, 2n) cross sections. Experimental and literature data were also compared with the present systematics.